Confidentiality and Informed Consent: School Counsellors Perceptions of Ethical Practices - Lehr, Ron; Lehr, Andria; Sumarah, John (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents the findings of in-depth interviews with school counsellors in Nova Scotia on issues related to confidentiality and informed consent. Of the 224 school counsellors in the province, 43 counsellors, representing all school boards, agreed to a 45-minute semi-structured telephone interview focusing on their current practices and their views on optimal practices related to confidentiality and informed consent. Analysis of interviews identified five categories of issues and concerns related to confidentiality and informed consent: informing students on issues of confidentiality, age of consent, issues of professional confidentiality, sharing client information with others, and confidentiality with teachers and principals.